Conference with Experts from the Rand Corporation on the Issues of National Security (Czech Journal of International Relations, 1992)
The international contacts of the úMV continued to develop intensively in 1991. A number of guests of the institute belonged to the world's best in their fields. On days 5-7 In May 1991, the úMV organized a conference together with the RAND Corporation, which was attended by several prominent figures in American research on military policy and national security. Although the topic of this colloquium was a rather narrow and specific issue of civil-military relations and the decision-making process on national security in the USA and Czechoslovakia, its course provided sufficient space for discussion of more general issues of the current security situation in Europe and the perspectives of its development.The American side attached considerable importance to the conference. This is evidenced by the composition of her delegation. It was led by the president of the RAND Corporation, J. Thomson. Among the participants from this institution were vice president G. Donohue and scientific staff from the department of international politics F. S. Larrabee, S. Popper, J. B. Steinberg and T. S. Szayna. The military part of the American delegation consisted of the head of the group for policy and programs of the political department of the High Command of the Allied Armed Forces of NATO in Europe, gen. major W. Freeman, Deputy Director for Planning in the Secretariat of the Deputy Chief of Staff for Planning and Operations, US Air Force Brig. gen. B. L. Mitchell, head of the East European policy section of the same workplace, major. D. Palendech and deputy chief of the intelligence staff of the High Command of the American Army in Europe, gen. major C. Pfister. The four-star general of the US Air Force in the reserve, R.H. Reed, who represented the American National Association for Training (in active service he was chief of staff of the Allied High Command) was also in the delegation NATO armed forces in Europe). The civilian part of the delegation also included J. A. Baker, a member of the US Atlantic Council, W. Christman, political assistant for the USSR and Eastern Europe to the Deputy Secretary of Defense for Policy, W. B. Slocombe, former US Deputy Assistant Secretary of Defense for Policy Planning, and W. Taylor, special deputy adviser for the security of the US ambassador to NATO. The delegation also included the director of the Radio Free Europe/Svoboda Research Institute, A. R. Johnson, and Vladimír Kusin, chief analyst of the analytical and research department of this institute.